2001
DOI: 10.1097/00043764-200109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Historical Cohort Study of US Man-Made Vitreous Fiber Production Workers: I. 1992 Fiberglass Cohort Follow-Up: Initial Findings

Abstract: This 1986 to 1992 update and expansion of an earlier historical cohort study examined the 1946 to 1992 mortality experience of 32,110 workers employed for 1 year or more during 1945 to 1978 at any of 10 US fiberglass (FG) manufacturing plants. Included are (1) a new historical exposure reconstruction for respirable glass fibers and several co-exposures (arsenic, asbestos, asphalt, epoxy, formaldehyde, polycyclic aromatic hydrocarbons, phenolics, silica, styrene, and urea); and (2) a nested, matched case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 25 publications
0
35
0
1
Order By: Relevance
“…However, evidence exists that some workers from at least one of the 10 NCI formaldehyde plants (Plant 1) had possible occupational or non-occupational exposures to potential NPC risk factors outside of the plant (Marsh et al, 1996(Marsh et al, , 2002). Moreover, our experience with other multi-plant studies, such as our study of man-made mineral Wber workers (Marsh et al, 2001a) and our reanalysis of the NCI cohort study of acrylonitrileexposed workers (Marsh et al, 2001b) has found that one or more sites with unique confounding exposures are heavily inXuencing the exposure-response analysis. When such plant-speciWc, potential confounding exposures are present, a detailed evaluation of single plants is essential to a full understanding of the exposure-response relationship (or lack thereof) in question, and hence, was a major focus of our reanalysis.…”
Section: Discussionmentioning
confidence: 89%
“…However, evidence exists that some workers from at least one of the 10 NCI formaldehyde plants (Plant 1) had possible occupational or non-occupational exposures to potential NPC risk factors outside of the plant (Marsh et al, 1996(Marsh et al, , 2002). Moreover, our experience with other multi-plant studies, such as our study of man-made mineral Wber workers (Marsh et al, 2001a) and our reanalysis of the NCI cohort study of acrylonitrileexposed workers (Marsh et al, 2001b) has found that one or more sites with unique confounding exposures are heavily inXuencing the exposure-response analysis. When such plant-speciWc, potential confounding exposures are present, a detailed evaluation of single plants is essential to a full understanding of the exposure-response relationship (or lack thereof) in question, and hence, was a major focus of our reanalysis.…”
Section: Discussionmentioning
confidence: 89%
“…Tampoco encontraron relaci贸n con el tiempo de exposici贸n ni con el periodo de latencia, incluso pudieron observar que los trabajadores con un tiempo de exposici贸n menor presentaban mayor riesgo de padecer un c谩ncer de pulm贸n que los que se hab铆an encontrado expuestos a periodos m谩s prolongados 38 . Este mismo autor realiz贸 en 2001 un estudio de casos y controles sobre una poblaci贸n americana perteneciente a diez industrias relacionadas con la producci贸n de FMA para estudiar el riesgo de desarrollar un c谩ncer de pulm贸n, sin que se obtuvieran incrementos significativos de este tipo de tumores en la poblaci贸n expuesta.…”
Section: Fibras De Vidrio De Filamento Continuo Y C谩ncer De Pulm贸nunclassified
“…The PubMed search of asphalt workers resulted in more than 20 cohort studies (some with overlapping populations), (10,28,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)68,69) 11 case-control studies, (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61) and 7 proportionate mortality studies. (2,(62)(63)(64)(65)(66)(67) From this group of peer-reviewed epidemiological studies, the subset that specifically included roofers was identified, and the abstracted characteristics are presented by study type in Table I.…”
Section: Epidemiological Studies Of Roofersmentioning
confidence: 99%